2020
DOI: 10.1016/j.ijlp.2020.101634
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the impact of revised mental health legislation on human rights in Queensland, Australia

Abstract: The Convention on the Rights of Persons with Disabilities (2006) (CRPD) has been instrumental for initiating and shaping the reform of mental health legislation in many countries, including the eight Australian jurisdictions. Multiple approaches have been proposed to assess and monitor the compliance of States Parties' mental health legislation with the CRPD, and to evaluate its success in protecting and promoting the human rights of people with disabilities. This article reports an effort to index the impact … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Well-intentioned legal protection for human rights can have unintended adverse consequences. In Queensland, an evaluation of revised MH legislation found that compulsory treatment orders actually increased after revised legislation despite efforts towards less restrictive treatment [ 83 ]. The COVID-19 pandemic added complexity to the problem of human rights protections for those with and even without mental illnesses particularly due to the strict enforcement of quarantine measures and rules [ 80 ].…”
Section: Contemporary Priorities For Global Mental Healthmentioning
confidence: 99%
“…Well-intentioned legal protection for human rights can have unintended adverse consequences. In Queensland, an evaluation of revised MH legislation found that compulsory treatment orders actually increased after revised legislation despite efforts towards less restrictive treatment [ 83 ]. The COVID-19 pandemic added complexity to the problem of human rights protections for those with and even without mental illnesses particularly due to the strict enforcement of quarantine measures and rules [ 80 ].…”
Section: Contemporary Priorities For Global Mental Healthmentioning
confidence: 99%
“…They robustly present the conditions for this, as well as the mitigating circumstances. Countries seeking exceptions to these guidelines perpetuate human rights violations, making it morally and ethically unacceptable (Gill et al, 2020). My country has unlawfully detained refugees for many years and my own state refused to provide facility access to UN human rights delegations (Amnesty International, 2013).…”
Section: The Uncomfortable Realitymentioning
confidence: 99%
“…This is despite nationwide reform of mental health legislation intended to improve the human rights of people with mental illness following the country’s adoption of the United Nations Convention on the Rights of Persons with Disabilities ( Callaghan and Ryan, 2012 ). However, legislative changes have had minimal impact on the high rates of CTO use in Australia ( Gill et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%